(untitled) (Wudil Journal of Science and Technology Education, 2025)
Agelanthusdodoneifolius (Loranthaceae), a hemi-parasitic plant widely utilized in Northern Nigerian ethnomedicine for treating malaria, wounds, and infections, was evaluated for its phytochemical composition and in vitro bioactivities to validate its traditional use. Aqueous, chloroform, and ethanol leaf extracts were subjected to qualitative phytochemical screening, revealing tannins, glycosides, saponins, phenols, and flavonoids, but lacking alkaloids, anthraquinones, and phlobatannins. In vitro antimalarial activity against Plasmodium falciparum (5% parasitemia) was determined using the Giemsa staining method. The chloroform and ethanol extracts exhibited dose- dependent activity, with the chloroform extract achieving 84.7% parasite elimination at 10 mg/mL after 48 hours—significantly higher than the ethanol extract (82.4%, p = 0.0145), though less potent than artemether (92.7%). Antimicrobial activity, assessed via the broth microdilution method against Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Candida albicans (ATCC 10231), revealed minimum inhibitory concentrations of 0.625–5 mg/mL for ethanol extracts and 1.25–10 mg/mL for chloroform extracts, supporting its traditional application in wound healing. Antioxidant activity determined by the DPPH assay showed IC₅₀ values of 0.45 ± 0.03 mg/mL (ethanol) and 0.82 ± 0.05 mg/mL (chloroform), indicating strong radical scavenging potential compared to ascorbic acid (0.02 ± 0.01 mg/mL). These findings validate the ethnomedicinal relevance of A. dodoneifolius and underscore its potential as a source of antimalarial, antimicrobial, and antioxidant agents. Further work should isolate its bioactive constituents, elucidate mechanisms of action, and evaluate in vivo efficacy for therapeutic development.